Morphological conservation of rays in the genus Rhinoptera (Elasmobranchii, Rhinopteridae) conceals the occurrence of a large batoid, Rhinoptera brasiliensis Müller, in the northern Gulf of Mexico - Jones, Christian M.; Hoffmayer, Eric R.; Hendon, Jill M.; Quattro, Joseph M.; Lewandowski, Justin; Roberts, Mark A.; Poulakis, Gregg R.; Ajemian, Matthew J.; Driggers, William B. Iii; Carvalho, Marcelo R. De; Rêgo, Mariana G.; Hazin, Fábio H. V.; et al. (Zootaxa, 2017)
In 2007, three rays identified as Rhinoptera brasiliensis based on tooth series counts were captured in the northern Gulf of Mexico, a region far outside their accepted range of the coastal waters of southern Brazil. Genetic analyses confirmed that these individuals were distinct from R. bonasus, the only recognized indigenous rhinopterid in the Gulf of Mexico. Further analyses of over 250 specimens confirmed the widespread occurrence of two species in the northern Gulf of Mexico and revealed that the anomalous individuals related most closely to vouchered specimens of R. brasiliensis from Brazil. Discriminant function analyses of morphological data identified several potential discriminating characters, but the degree of overlap of the measurements and counts between the two species rendered most impractical for identification purposes. However, the shape of the supracranial fontanelle appeared to be consistently reliable in differentiating between the two species. Tooth series counts (R. bonasus = 5 to 15, R. brasiliensis = usually 7 to 13) were significantly different between the two species but exhibited considerable overlap. This is the first study to verify the occurrence of R. brasiliensis in the northern Gulf of Mexico; however, the close genetic relationships to other rhinopterid species, as well as the morphological similarity of the group as a whole, require additional research.